Pollinators drive floral evolution in an Atlantic Forest genus. Issue 5 (22nd August 2020) - Neves, Beatriz; Kessous, Igor M; Moura, Ricardo L; Couto, Dayvid R; Zanella, Camila M; Antonelli, Alexandre; Bacon, Christine D; Salgueiro, Fabiano; Costa, Andrea F
Abstract: Pollinators are important drivers of angiosperm diversification at both micro- and macroevolutionary scales. Both hummingbirds and bats pollinate the species-rich and morphologically diverse genus Vriesea across its distribution in the Brazilian Atlantic Forest. Here, we (i) determine if floral traits predict functional groups of pollinators as documented, confirming the pollination syndromes in Vriesea and (ii) test if genetic structure in Vriesea is driven by geography (latitudinal and altitudinal heterogeneity) or ecology (pollination syndromes). We analysed 11 floral traits of 58 Vriesea species and performed a literature survey of Vriesea pollination biology. The genealogy of haplotypes was inferred and phylogenetic analyses were performed using chloroplast ( rps16-trnk and matK ) and nuclear ( PHYC ) molecular markers. Floral traits accurately predict functional groups of pollinators in Vriesea . Genetic groupings match the different pollination syndromes. Species with intermediate position were found between the groups, which share haplotypes and differ morphologically from the typical hummingbird- and bat-pollinated flowers of Vriesea . The phylogeny revealed moderately to well-supported clades which may be interpreted as species complexes. Our results suggest a role of pollinators driving ecological isolation in Vriesea clades. Incipient speciation and incomplete lineage sorting may explain the overall low genetic divergence within and among morphologically defined species, precluding the identification of clear species boundaries. The intermediate species with mixed floral types likely represent a window into shifts between pollinator syndromes. This study reports the morphological-genetic continuum that may be typical of ongoing pollinator-driven speciation in biodiversity hotspots. Abstract : In this study, we show floral traits to accurately predict hummingbird and bat pollinators in the Atlantic Forest genus Vriesea . Genetic groupings match the different pollination syndromes. We identify species with intermediate genetic position which differ morphologically from the typical hummingbird- and bat-pollinated Vriesea flowers by their mixed floral traits. We suggest a role of pollinators driving ecological isolation in Vriesea clades and that intermediate species likely represent a window into shifts between pollinators.